Pointwise lower bounds in growth spaces with little $o$ conditions - Cuckovic, Zeljko; Taskinen, Jari (Mathematica Scandinavica, 2025)
Pointwise lower bounds on the open unit disc $\mathbb{D} $ for the sum of the moduli of two analytic functions $f$ and $g$ (or their derivatives) are known in several cases, like $f,g$ belonging to the Bloch space $\mathcal{B} $, BMOA or the weighted Hardy space $H_ω ^∞ $. We modify the proofs of two important cases, proved by Ramey-Ullrich and Abakumov-Doubtsov, for functions with little $o$ growth conditions.